Some Useful Properties of Log-Logistic Random Variables for Health Care Simulations - Clark, David E.; El-Taha, Muhammad (International Journal of Statistics in Medical Research, 2015)
A log-logistic (LL) random variable is one whose logarithm has a logistic distribution. Since the logistic distribution is similar to the normal distribution, log-logistic random variables are similar to log-normal (LN) random variables. However, many of the important properties of LN random variables can only be described using integrals, while the corresponding properties of LL random variables can be described using simple algebra. LL random variables may therefore be a useful alternative to LN random variable for computer simulation of operating room processes or other health care applications, especially when they fit the data more closely. We review the properties of LL random variables, and derive some relationships of the mean residual time to the median residual time. We describe methods of fitting LL distributions to observed data, and discuss potential advantages of using them for simulation of operating room utilization.